PEWARISAN KEARIFAN LOKAL TARIAN TOPENG BAPANG DI SDN MERJOSARI 1 KOTA MALANG - Kamaria, Kamaria; Sugiharto, Firsta Bagus; Anwar, Moh. Farid Nurul; Rozhana, Kardiana Metha; Surandoko, Tomas (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to describe the process of transmitting local wisdom through the learning of the Topeng Bapang Dance at SDN Merjosari I Kota Malang, considering the importance of preserving traditional culture amid globalization that threatens the continuity of local values. This research employs a qualitative case study method with data collected through observation, in-depth interviews, and documentation related to extracurricular dance activities at the school. Data analysis uses a qualitative approach with interactive techniques including data reduction, data display, and conclusion drawing. The findings indicate that the transmission of the Topeng Bapang Dance is conducted systematically through participatory learning methods involving students actively in rehearsals and performances, thereby enhancing their understanding of cultural values and fostering love and pride for local heritage. However, challenges exist, such as limited facilities and initially low interest among some students who are more inclined toward modern popular culture. To address these issues, the school collaborates with art communities and parents to support activities through the provision of infrastructure and strengthening cultural appreciation. In conclusion, the preservation of local wisdom through traditional arts education in elementary schools is effective when supported by collaboration among various parties and facility improvements.